The Effect of Servant Leadership Education on Police Job Satisfaction at the Singkawang Police Station - Padma Anggarini, Ida Ayu Made Risma; Bratasena, I Gede Nyoman; Halimah, Halimah; Earlyanti, Novi Indah (Journal of English Language and Education, 2025)
This study focuses on the influence of Polri Servant Leadership education on the job satisfaction of Polri personnel at Polres Singkawang. This study was motivated by complaints from Polri personnel about the leadership style applied by their superiors. The purpose of this study was to determine how much influence Polri Servant Leadership education has on the job satisfaction of Polri personnel at Polres Singkawang. This study uses a quantitative approach with a survey method by distributing questionnaires to Polres Singkawang personnel. The sampling technique in this study is simple random sampling with a total of 385 respondents. Data analysis was carried out using a simple linear regression technique in the form of a model goodness-of-fit test, partial test (t-test), and coefficient of determination. The theories and concepts used include Polri Servant Leadership and Job Satisfaction. The results of the study showed that the level of Polri Servant Leadership at Polres Singkawang was quite high with an average value of 4.5 points. The level of job satisfaction of Polres Singkawang personnel from the seven dimensions tested in this study on the nature of work dimension with a score of 5.39. The results of the data analysis show that Servant Leadership Polri can influence the job satisfaction of Polri personnel at Polres Singkawang by 32.0% with a beta coefficient value of 0.515 (positive), it can be concluded that Servant Leadership Polri has a positive and significant effect on the job satisfaction of Polri personnel at Polres Singkawang. Thus, it is important to have education on the application of servant leadership for Polri with the aim of increasing the job satisfaction of its personnel.